The impact of the Corona pandemic on women's rights in Iraq (قضايا سياسية, 2023)
Women in Iraq are exposed to a global epidemic whose repercussions affect all economic, social, and health aspects. The study deals with the challenges caused by the pandemic and the repercussions that resulted from the Iraqi government’s measures required by circumstances to confront them, such as the ban and disruption of economic and social activities that have cast their shadow on the effectiveness of all segments of society, including women. These factors have had profound social and economic repercussions, which have hurt women in Iraq, including their mental health, and have led to the rise of cases of domestic violence. Further, the effects of the pandemic have impacted women's social status, education and health care. Although it is difficult to establish a direct comparison between before and after the pandemic due to the conditions that the pandemic necessitated, it can be said that the challenges and obstacles that are rooted, are a result of the policies pursued by the Iraqi government. Yet, the pandemic also highlighted matters that had been considered relatively less important in previous years, such as the impact of traditional values on young girls.